Pyometra and Sertoli cell tumor in a dog with persistent Müller duct - Cahua U., Jacqueline (2015)
Persistent Mullerian duct (PMDS) is a type of hereditary male pseudohermaphroditism observed in several dog breeds. Males have testes and XY chromosomes in addition to oviduct cranial vagina, uterus and bilateral Müllerian duct derivatives. In the present study is described the case of a 8-year Schnauzer dog, phenotypically male, with a history of anorexia, lethargy and tenesmus during the last two days. The pet had male genitalia but evident right lateral cryptorchidism; however, ultrasound examination revealed that the animal had remnants of the duct Muller (uterine body and horns) with an infectious process compatible with pyometra. The blood smear showed polymorphonuclear cells without corpuscles of Barr. A tumor mass was found cranial to the right uterine horn and corresponded to a testicular neoplasia of Sertoli cells. The left testicle was located in the scrotal sac and was hypoplastic.